Supply Chain in Digital Operation Model for Student Loan Fund Management for Higher Education in Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The research aims to design supply chain in digital  operation model  for  student Loan Fund managementfor higher education in Thailand, and evaluate  the developed model. The research procedures divide into two phases. The first phase is to design supply chain in digital  operation model  for  student Loan Fund management for higher education in Thailand and the second phase is to evaluate the developed model. The sample group in study consists of ten experts. Selected by purposive sampling. Data were analysed by arithmetic mean and standard deviation. The research result are seven main components, namely Su-components, Suppliers, Service provider, education customers, Consumers, satisfaction and feedback. All experts agree supply chain in digital operation model  for  student loan fund management for higher education in Thailandis high level of appropriateness.